On the modularity of a lattice of $τ$-closed $n$-ultiply $ω$-composite formations - Vorob'ev, N. N.; Tsarev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
Let $n ≥ 0$, let $ω$ be a nonempty set of prime numbers and let $τ$ be a subgroup functor (in Skiba’s sense) such that all subgroups of any finite group $G$ contained in $τ (G)$ are subnormal in $G$. It is shown that the lattice of all $τ$-closed $n$-multiply $ω$-composite formations is algebraic and modular.